Diffuse Neutron Scattering of KBr at Room Temperature and Its Application as Background Function in Rietveld Analysis - Khairul Basar; Xianglian Xianglian; Takashi Sakuma; Haruyuki Takahashi; Naoki Igawa (Institute for Research and Community Services (LPPM) ITB, 2009)
Diffuse neutron scattering from powder KBr was measured at room temperature. The oscillatory diffuse scattering is clearly observed. The diffuse scattering theory including correlation effects among thermal displacements of atoms is applied to background function in the Rietveld analysis. The observed scattering data are analyzed by including the correlation effects among thermal displacements of first, second and third nearest neighboring atoms. The inter-atomic distance and temperature dependence of the values of correlation effects is discussed.